Zum Einfluss mitgehandelter Zahlungsansprüche auf die Kauf- und Pachtpreise von Ackerland in Schleswig-Holstein; The Impact of Payment Entitlements on Arable Land Prices and Rental Rates in Schleswig-Holstein - Solveigh Hennig; Gunnar Breustedt; Uwe Latacz-Lohmann (German Journal of Agricultural Economics (GJAE), 2014)
– This paper investigates the impact of payment entitlements traded in conjunction with farmland on the prices and rental rates of arable land. The empirical analysis is based upon a survey of land rental and land purchase contracts concluded in Schleswig-Holstein between 2005 and 2011. Regression analysis is used to estimate the impact of plot attributes, farm characteristics, regional and macroeconomic factors on arable land purchase prices and rental rates. The simultaneous transfer of payment entitlements enters the models as an additional explanatory variable. The observation period is sub-divided into two phases to account for the potentially differential impact of payment entitlements before (until 2009) and during the gliding phase (2010 and after). The sample comprises 135 land purchase contracts and 213 land rental agreements. The results show that rental rates for arable land in Schleswig-Holstein, besides being influenced by other factors, are significantly higher when a payment entitlement is traded with the land. The price-increasing effect is estimated to be on average 30-35 % of the payment entitlements' nominal value at the time of contract conclusion. The analysis does not reveal a statistically significant impact of payment entitlements on the purchase price of arable land.
Keywords: 330